Important insect and mite pests of carnation in Himachal Pradesh and their management - Sharma, Pankaj; Chandel, V. G. S.; Verma, S. C.; Singh, Chander (Indian Horticulture, 2024)
Carnation is an important floricultural crop grown globally as well as in Himachal Pradesh for cut flowers. It is well known for its beautiful, attractive and fragrant flowers. It is an important source of economy for the farmers of Himachal Pradesh in protected cultivation. It is infested by a wide range of pests like insect pests, mites and nematodes. Tetranychus urticae, Helicoverpa armigera, Myzus persicae and thrips infest this crop in mid-hill conditions of Himachal Pradesh. This article contains information regarding damage symptoms and management strategies against these pests of carnation which will be beneficial for farmers in identifying and managing these pests and preventing economic damage.